The inflammasome NLRP3 plays a protective role against a viral immunopathological lesion. Issue 5 (29th October 2015) - Gimenez, Fernanda; Bhela, Siddheshvar; Dogra, Pranay; Harvey, Lorena; Varanasi, Siva Karthik; Jaggi, Ujjaldeep; Rouse, Barry T
Abstract : NLRP3 inflammasome in SK pathogenesis. Abstract: Herpes simplex 1 infection of the eye can cause blindness with lesions in the corneal stroma largely attributable to inflammatory events that include components of both adaptive and innate immunity. Several innate immune responses are triggered by herpes simplex 1, but it is unclear how such innate events relate to the subsequent development of stromal keratitis. In this study, we compared the outcome of herpes simplex 1 ocular infection in mice unable to express NLRP3 because of gene knockout (NLRP3 −/− ) to that of wild-type mice. The NLRP3 −/− mice developed more-severe and earlier stromal keratitis lesions and had higher angiogenesis scores than did infected wild-type animals. In addition, NLRP3 −/− mice generated an increased early immune response with heightened chemokines and cytokines, including interleukin-1β and interleukin-18, and elevated recruitment of neutrophils. Increased numbers of CD4 + T cells were seen at later stages of the disease in NLRP3 −/− animals. Reduction in neutrophils prevented early onset of the disease in NLRP3 −/− animals and lowered levels of bioactive interleukin-1β but did not lower bioactive interleukin-18. In conclusion, our results indicate that NLRP3 has a regulatory and beneficial role in herpetic stromal keratitis pathogenesis.